Views on Legal Perspectives on John Austin's Thoughts - Ade Rizki Saputra; Hj. Hernawati Ras; Hj. Yeti Kurniati (Formosa Journal of Sustainable Research, 2023)
John Austin's thoughts on positive law have played a central role in the development of positive legal theory and the concept of the rule of law. However, his highly formalistic view, with its emphasis on law as commandment without including moral and ethical aspects, has received significant criticism. This article analyzes the influence of Austin's thought on modern legal understanding and how criticism of his approach has guided the development of a more inclusive and civilized theory of positive law. This discussion highlights the need to integrate aspects of morality in lawmaking and recognize the complexity of the relationship between law, morality, and justice in modern society. Recommendations are presented to encourage the development of a more balanced theory of positive law and ensure that enacted laws reflect broader ethical values